2010
DOI: 10.1186/1471-2407-10-594
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of depression and anxiety in adult cancer outpatients: a cross-sectional study

Abstract: BackgroundThe prevalence of anxiety and depressive disorders in cancer patients and its associated factors in Pakistan is not known. There is a need to develop an evidence base to help introduce interventions as untreated depression and anxiety can lead to significant morbidity. We assessed the prevalence of depression and anxiety among adult outpatients with and without cancer as well as the effect of various demographic, clinical and behavioral factors on levels of depression and anxiety in cancer patients.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
83
3
10

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 36 publications
9
83
3
10
Order By: Relevance
“…In oncology, patients' lives are changed after diagnosis and treatment; moreover, each patient responds differently to situations experienced during hospitalization, which can generate anxiety (2)(3) . This was the case for the subjects of this study, who required hospitalization in order to receive continuous intravenous chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In oncology, patients' lives are changed after diagnosis and treatment; moreover, each patient responds differently to situations experienced during hospitalization, which can generate anxiety (2)(3) . This was the case for the subjects of this study, who required hospitalization in order to receive continuous intravenous chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients often experience pain and anxiety that may exceed their coping mechanisms. Previous studies suggest that several factors, including cancer diagnosis and interventional procedures, contribute to psychological distress of patients (Massie et al, 2004;Martin et al, 2005;Schupp et al, 2005;Sims et al, 2006;Wang et al, 2008;Jadoon et al, 2010;Hulbert-Williams et al, 2011). Minagawa et al (1996) and Godding et al (Aqarwal et al, 2010) reported that about 30% -60% cancer patients have psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…For the patients, there are many physical and social factors that that may compound the diagnosis of hepatic carcinoma, making it more difficult to cope and contemplate different treatment options. It is demonstrated a stressful and life-changing event causing significant psychological distress (Jadoon et al, 2010;Pirl et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A er a cancer diagnosis is disclosed, the physical and psychological changes that are triggered by cancer are evident and have signifi cant eff ects, leading primarily to anxiety and depression (2) . These psychological condi ons o en persist throughout treatment and may be related to the treatment's side eff ects.…”
Section: Introductionmentioning
confidence: 99%